Antimicrobial susceptibility patterns of Bacterial Isolates from patients attending Ear, Nose, and Throat Department of a Tertiary Care Hospital in Burdwan, West-Bengal, India. - Ghosh , Purbasha; Mukherjee , Tapajyoti; Dasgupta , Arindam; Ghosh , Poulami; Banerjee , Sohini; Nag , Soumi; Syeda Azra Zabin; Das , Soumendranath (International Journal of Endorsing Health Science Research, 2022)
Background: The susceptibility of the most common causative pathogens drives empiric initial antibiotic therapy for bacterial infections. This cross-sectional study was conducted to detect the infection trends and antibiotic susceptibility patterns of patients attending the Burdwan medical college and hospital (BMCH), West Bengal. Methodology: A prospective study was conducted for six months, from August 2021 to January 2022, at the department of microbiology (BMCH), West Bengal. Isolation of bacteria and fungus was performed from clinical samples obtained from patients attending the department of the ear, nose, and throat (ENT) of BMCH. A total of 84 samples were collected from patients with suspected ENT infections. Types of samples taken include pus, fluid, tissue, and throat, nasal, and ear swabs. Results: Bacterial growth was observed in 55(65.47%), of which gram-positive and gram-negative bacterial isolates were found in 31(56.36%) and 21(38.18%) samples, respectively. 3(5.45%) gram-positive bacilli were grown, and 14(16.66%) samples were positive for fungal growth. Conclusion: Antibiogram of gram-positive isolates showed maximum susceptibility to vancomycin and least to ciprofloxacin, whereas gram-negative isolates showed maximum susceptibility to amikacin and least to ciprofloxacin.